Floating Neutral Detection Using Actual Generation of Form 2S Meters - I. Vicente; A. Arrinda; J. E. Rodriguez-Seco; L. Piyasinghe (IEEE Open Access Journal of Power and Energy)
In the low-voltage distribution system of the USA, Canada and some countries of Central and South America, the most used configuration is the single-phase three-wire system (120 V/240 V) also known as the split-phase distribution system. When the neutral wire of the distribution system gets damaged or broken the current returns through the ground and a floating neutral condition arises. Service to the house continues without interruptions because no high over-currents come up. If the return path impedance is high enough, the equally balanced voltage system gets shifted, going out of boundaries and causing malfunctions in the appliances or even fire. A new classification-based detector is proposed to detect this condition, which only needs current measurements that the actual generation of form 2S meter gathers. Moreover, due to the simplicity of the algorithm, it can be embedded in the current generation of meters, which represents great potential of the detector. To that end, the low-voltage distribution system is modelled using a real database and some assumptions are made. The proposed novel detector approach shows zero false alarms in the houses tested and a detection time that allows the fault to be detected before significant damage occurs to the house.